Associations of Phthalate Metabolites and Obesity-Related Metabolic Factors - Wang, MD, PhD, Lu; Zhang, PhD, Xi; Song, MD, ScD, Yiqing (North American Journal of Medicine and Science, 2017)
Diabetes and obesity have reached epidemic rates in most developed and developing countries. Over-nutrition and physical inactivity are established risk factors with key roles in the etiology of type 2 diabetes. However, these factors alone cannot fully account for either the rate or the magnitude with which diabetes has increased worldwide. Research on whether exposure to environmental endocrine disrupting chemicals (EDCs) may be a preventable risk factor for diabetes development has attracted considerable attention since the 1990s. Phthalates are a group of EDCs characterized by widespread human exposure; concerns about the adverse effects of exposure to phthalates on human health are increasing. Early studies regarding the toxicity of phthalates largely focused on reproductive health and development effects. More recent research has shifted towards possible metabolic effects that may increase the risk for obesity, insulin resistance, diabetes, and other related adverse health outcomes. Considering the ubiquity of phthalates in the environment, it is important to understand the potential hazards of these chemicals even at very low exposure levels; if those are confirmed, strategies must be developed to remove them from the environment or at least preclude widespread contamination. This review aimed to summarize current evidence on the potential hazards of phthalates with regard to metabolic disease and highlighted the importance of further investigation that will have high public health significance for both developed as well as developing countries, where the exposure may continue to be high for decades to come. [N A J Med Sci. 2017;10(2):88-93. DOI: 10.7156/najms.2017.1002088]